1989
DOI: 10.1002/mrc.1260270908
|View full text |Cite
|
Sign up to set email alerts
|

13C NMR studies of insulin. Part I—Spectral assignments

Abstract: Natural abundance 75 MHz I3C NMR spectral assignments are reported for bovine and porcine zinc insulin in solution. A large number of protein resonances are well resolved, and approximately 80% of these have been assigned to either residue types or to specific sites within the protein. Assignment techniques included consideration of free amino acid or peptide shifts, pH studies and comparison of sequence and spectral differences between bovine and porcine insulin, in addition to the use of NMR relaxation times… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1991
1991
1996
1996

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…within a radius of about 1 nm) it accelerates the relaxation of the proton spin drastically, giving rise to a broadened NMR line. The extent of the linewidth increase varies as r-6 (r-distance between proton and paramagnetic ion) [7]. From the fact that there is only one uniform set of spectra with certain specifically broadened peaks it must be concluded that there is a rapid exchange (on the NMR timescale) between bound and free Mn2+ ions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…within a radius of about 1 nm) it accelerates the relaxation of the proton spin drastically, giving rise to a broadened NMR line. The extent of the linewidth increase varies as r-6 (r-distance between proton and paramagnetic ion) [7]. From the fact that there is only one uniform set of spectra with certain specifically broadened peaks it must be concluded that there is a rapid exchange (on the NMR timescale) between bound and free Mn2+ ions.…”
Section: Resultsmentioning
confidence: 99%
“…The 5' and 2' OH groups of ribose were protected by 4,4'-dimethoxytrityl and tert-butyldimethylsilyl protecting groups, respectively. Protection of the exocyclic amines in adenine and guanine was achieved by dimethylaminomethylene protection groups [7,8]. The purification of the oligonucleotides was performed by HPLC on a Vydac C4 column.…”
Section: Oligoribonucleotide Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…The resonances of protons in the vicinity of paramagnetic probes were broadened with the excess linewidth varying as r-6, where r is the distance between ion and proton (11). Hence, there is a preferred binding site for Mn2+ and, correspondingly, for Mg2+ in the vicinity ofbp 2 and 3.…”
Section: Chemical-shiftmentioning
confidence: 99%
“…These were different in magnitude and sign for the individual base pairs for the duplexes with and without an ACCA end. To check whether these small differences in chemical shift of NH resonances are related to variations in divalent ion binding affinity along (11,12). The imino resonance regions of the proton NMR spectra of the 14-mer and the 18-mer before and after addition of MnCl2, respectively, are presented in Fig.…”
Section: Chemical-shiftmentioning
confidence: 99%